ANALISIS PELAKSANAAN PROGRAM TB PARU DI WILAYAH KERJA PUSKESMAS SUNGAI SALAK KABUPATEN INDRAGIRI HILIR TAHUN 2023 - Anwar, Anwar; Susmaneli, Herlina; Alamsyah, Agus; Dewi, Oktavia; Rustam, Musfardi (Ensiklopedia of Journal, 2024)
The World Health Organization (WHO) 2021 stated that tuberculosis is still one of the main world health problems where tuberculosis is the 13th leading cause of death in the world and in 2020 tuberculosis became the infectious disease that caused the most deaths in the world after COVID-19. The National Strategy for Tuberculosis Prevention in Indonesia 2020-2024 explained that the scope of finding tuberculosis patients has not reached the target. Based on the Health Profile of the Salak Health Center in 2021, the achievement of the Pulmonary Tuberculosis program (Incidince Rate) was 21 suspected patients or 10.6% of the target of 198 suspected patients. The purpose of the study was to analyze the low number of passive and active case finding, and analyze community empowerment towards the implementation of the Pulmonary Tuberculosis Program in the Working Area of the Sungai Salak Community Health Center. This type of research is qualitative, descriptive, with a case study design. The research location is in the Working Area of the Sungai Salak community health center, Indragiri Hilir Regency. The research period is January to August 2023. In-depth interview research informants there were 5 people consisting of 3 main informants (tuberculosis Program Holders at Puskesmas, Analysts, Doctors) and 2 Supporting In-Informants (Head of Puskesmas and Tuberculosis Program Holders at the Health Office), while the Focus Group Discussion informants there were 6 people consisting of village heads, RT leaders, RW leaders, community leaders, PMOs, tuberculosis cadres. The form and flow of passive examination of tuberculosis patients are in accordance with the SOP. The obstacle is that sometimes patients who come for treatment to the puskesmas find it difficult to remove their sputum at that time. Active case discovery has not been in accordance with Standard Operating Procedures (Screening and Household Contact of tuberculosis patients) because nothing has been done. It is expected that the role of tuberculosis officers can ensure that tuberculosis cases are reported regularly through the tuberculosis program information system.Keywords : Community Empowerment, Passive Case Discovery, Active Case Discovery, Sungai Salak Community Health Center, and Tuberculosis Program